2022
DOI: 10.37190/ppmp/157487
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of cyanidation after microwave roasting treatment on refractory gold/silver ores by characterization studies

Abstract: In this article, the efficiency of microwave pretreatment, which is an environmentally friendly, low-energy consuming method for recovery from refractory gold-silver ores, was investigated. The ore sample belonged to the oxidized Bolkardağ deposit, which contains carbonate (calcite, dolomite, smithsonite, hydrozincite), silicate (quartz, hemimorphite), sulfate (beudantite, plumbo-jarosite), and iron oxy/oxyhydroxide (hematite, limonite) minerals. Sulfur/sulfate-bearing silver and gold minerals are found either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The 1434.71 (1435.00) cm -1 peak suggested that ZnS formed on the smithsonite surface after the Na2S treatment (Hosseini and Forssberg, 2006). The peaks at 998.98 cm -1 and 875.59 cm -1 were a C-O stretching peak (MalligArjuna Rao et al, 2021) and a specific calcite peak (Luo et al, 2011;Kiefer et al, 2018), whereas the 909.57 cm -1 peak belonged to hydroxyl group bonds (Yoğurtcuoğlu, 2023c). The peaks at 797.00 cm -1 were the peaks of goethite (Zviagina et al, 2020) and quartz minerals (Ojima, 2003;Sbihi et al, 2014).…”
Section: The Feed Sample Characterization Analysesmentioning
confidence: 99%
“…The 1434.71 (1435.00) cm -1 peak suggested that ZnS formed on the smithsonite surface after the Na2S treatment (Hosseini and Forssberg, 2006). The peaks at 998.98 cm -1 and 875.59 cm -1 were a C-O stretching peak (MalligArjuna Rao et al, 2021) and a specific calcite peak (Luo et al, 2011;Kiefer et al, 2018), whereas the 909.57 cm -1 peak belonged to hydroxyl group bonds (Yoğurtcuoğlu, 2023c). The peaks at 797.00 cm -1 were the peaks of goethite (Zviagina et al, 2020) and quartz minerals (Ojima, 2003;Sbihi et al, 2014).…”
Section: The Feed Sample Characterization Analysesmentioning
confidence: 99%